Empirical analysis of adaptive market hypothesis using Sharpe Ratio for buy and sell opportunities in global indices - Raju, Ajay; Jagannathan, Uday Kumar; Pundalika, Triveni (The Economics and Finance Letters, 2025)
This study aims to investigate market efficiency and compare the profitability of the Sharpe Ratio Minimae and Maximae trading strategies with the buy-and-hold strategy across indices in different global markets. It tests the prevalence of the Adaptive Market Hypothesis (AMH) by analyzing cyclical variations in strategy performance. The research covers stock indices from six countries, analyzing monthly data spanning January 1998 to December 2023. A rolling window approach is adopted to evaluate time-varying performance and explore potential correlations with market inefficiency. Statistical tests are employed to examine the dynamics of the Sharpe Ratio and its role in investment decision-making and risk assessment. The findings reveal that the Sharpe Ratio Minimae and Maximae strategies consistently outperformed the buy-and-hold strategy across all indices. These strategies achieved higher returns per unit of risk, validating the Adaptive Market Hypothesis by highlighting cyclical variations in market profitability. The results confirm the superior performance of Sharpe Ratio-based strategies over the buy-and-hold approach, supporting the presence of evolving market efficiency in line with the Adaptive Market Hypothesis. The study provides actionable insights for investors and portfolio managers, emphasizing the importance of recognizing market inefficiencies and adopting adaptive strategies. Adjusting investment approaches based on changing market conditions can significantly improve risk-adjusted returns.